(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The article is concerned with solving development issues of feedback services from students about the education environment in higher educational establishment. Our research conducted at the chair of informatics, software engineering and economic cybernetics of Kherson State University.During 6 years (2009 -2015) at the chair conducts a survey of students about their level of satisfaction of the learning process and teachers’ evaluation by students. As a part of the study surveyed students of 1-4 courses of the chair of informatics, software engineering and economic cybernetics. All respondents were distributed to interested and disinterested in the survey. Implementation of service "KSU Feedback" at Kherson State University in the chair of informatics,software engineering and economic cybernetics positively influenced on the creation of education environment where university acts as the corporation of students servicing.